Seed dispersal by waterbirds in southern Africa: comparing the roles of ectozoochory and endozoochory. (1st February 2016) - Reynolds, Chevonne; Cumming, Graeme S.
Summary: Waterbirds are important seed dispersers and may play a vital role in maintaining connectivity among isolated aquatic communities. Whilst considerable progress has been made in our understanding of the dispersal function of waterbirds, the number of studies is still limited and is largely focused on migratory waterbirds in Europe. We present the first detailed study of seed dispersal by waterbirds in Africa. We quantified and compared endo‐ and ectozoochory across six waterfowl species at three widely dispersed sampling locations in South Africa and tested for differences between dispersal agents and sampling sites. We also tested for differences in the plant communities dispersed by endo‐ and ectozoochory. All intact and germinating propagules found in freshly collected faecal samples ( N  =   313) and feather brushings ( N  =   422) were counted and identified. A total of 1585 propagules from 48 plant taxa were recovered from the samples. Thirty‐seven per cent of all external brushings and 27% of all faecal samples contained at least one intact propagule and 15 and 8% of the samples contained at least one germinating propagule, respectively. Sampling site had a strong influence on the presence, abundance and germination of propagules recovered from both external and faecal samples. Additionally, sympatric waterfowl showed differences in the abundance and germinability of plant propagules transported by endozoochory. The presence of at least one propagule was highest in the external samples, but propagule abundance and germination were highest in faecal samples. The community composition of propagules transported by each of these two modes was significantly different, suggesting that endo‐ and ectozoochory are complementary dispersal mechanisms. Our results indicate an important role for waterbirds in the dispersal of aquatic plants in Africa. While ectozoochory can be an important dispersal mechanism, its effects may be heterogeneous and unpredictable relative to endozoochory. Endozoochory appears to be the more effective and dominant mechanism. Our results also point to a high capacity for the dispersal of exotic species via both ecto‐ and endozoochory.